2012
DOI: 10.1111/j.1468-232x.2011.00662.x
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Relations Climate and Union Commitment: An Evaluation of Workplace‐Level Effects

Abstract: The denitive version is available at wileyonlinelibrary.com Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 48 publications
(132 reference statements)
2
34
0
Order By: Relevance
“…This finding was congruent with the notion that employees who are commited to unions feel uncomfortable for being aligned with the organization and with the union simultanously (Redman & Snape, 2012). The result of this discomfort would be a deviation of employees' efforts, attachement, and engagement from the organization to union (Goeddeke & KammeyerMueller, 2010) reducing the level of job satisfaction of them.…”
Section: Findings and Discussionsupporting
confidence: 77%
“…This finding was congruent with the notion that employees who are commited to unions feel uncomfortable for being aligned with the organization and with the union simultanously (Redman & Snape, 2012). The result of this discomfort would be a deviation of employees' efforts, attachement, and engagement from the organization to union (Goeddeke & KammeyerMueller, 2010) reducing the level of job satisfaction of them.…”
Section: Findings and Discussionsupporting
confidence: 77%
“…Industrial relations climate refers to the degree to which the relationship between the union and management is perceived to be harmonious, respectful, and open (Snape & Redman, 2012). It has been suggested that the quality of the union-management relationship will influence union loyalty (Gallagher & Clark, 1989;Sherer & Morishima, 1989).…”
Section: Hypothesis 4: Union Socialization Will Have a Positive Effecmentioning
confidence: 99%
“…This is followed by employer hostility (B= 0.399), and the lowest is for trade union internal factors (B= 0.132; p<0.05). Kumar et al, 2013;Johari, 2014;Fiorito and Jarley, 2003;Ramasamy, 2010;Rose et al, 2011;Pyman, 2002 Industrial Relations Climate Snape andRedman, 2012;Pyman, 2004Employer Hostility Campolieti et al, 2013Gall and McKay, 2001;Cullinane andDundon, 2012 Union Membership Ramasamy, 2010;Rose et al, 2011;Kumar et al, 2013. .000 The purpose of the study is to identify the factors that contribute towards the declining trade union membership.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies demonstrated that the industrial relation climate may influence the unions in a positive way to sustain their membership (Magenau et al, 1988;Dastmalchian, 2008;Snape and Redman, 2012). According to Pyman et al (2010), industrial relations climate reflects the behaviour of people at workplace and also describes the relationship between employees, management and unions.…”
Section: Industrial Relations Climatementioning
confidence: 99%